Rapid and sustained response to immune checkpoint inhibition in cutaneous squamous cell carcinoma after allogenic hematopoietic cell transplant for sézary syndrome. Issue 1 (4th December 2019) - Khaddour, Karam; Musiek, Amy; Cornelius, Lynn A.; Dehdashti, Farrokh; Westervelt, Peter; Fields, Ryan; Ansstas, George
Abstract : Background: Cutaneous squamous cell carcinoma (cSCC) is not uncommon in association with indolent malignancies that were treated with prior radiotherapy and after allogenic bone marrow transplantation. On the other hand, cutaneous T-cell lymphoma (CTCL) is a subtype of non-Hodgkin's lymphoma which is characterized by an indolent course, with relative refractoriness to conventional chemotherapies and radiotherapy, and occasionally referred for allogeneic hematopoietic cell transplantation (allo-HCT). Recently, the use of immune checkpoint inhibitors has gained attention in the treatment of both cutaneous squamous cell carcinoma and hematological malignancies. However, many patients with hematological malignancies eventually undergo allo-HCT, raising the concern of potential adverse events (graft versus host disease) due to manipulation of the immune system with use of checkpoint inhibitors. Case presentation: We describe a patient with relapsed refractory CTCL (Sézary Syndrome) who underwent allo-HCT with persistence of disease post-transplant. The patient additionally developed a progressively worsening lesion on the right shoulder which was biopsied and showed poorly differentiated carcinoma (cSCC). Pembrolizumab was started for the treatment of cSCC. After second cycle of treatment, the cSCC lesion responded dramatically to the use of immune checkpoint inhibitor. Also, the patient experienced significant resolution of pruritus and generalized erythema. During 24 months of follow up after initial treatment with checkpoint inhibition immunotherapy, the patient showed durable response of both cSCC and CTCL, as well as restoration of full donor chimerism, without obvious worsening of graft versus host disease (GVHD). Conclusion: This is the first case to our knowledge of rapid and durable response of both cSCC and CTCL to immune checkpoint inhibition after allo-HCT. Although this report highlights the potential for significant response to this class of medication, further studies are required to confirm the efficacy and safety of this approach in patients with CTCL after allo-HCT given the potential concern of GVHD.